New method for measuring intimal component of pulmonary arteries. - Fernie, J M (1985)
Current methods for assessing the intima of pulmonary arteries produce measurements of intima and artery size that are affected by the constriction or collapse of the arteries and the generally patchy distribution of intimal abnormality. Our new method measures intimal area and defines artery size as the total length of the internal elastic lamina; these measurements are unaffected by the constriction or collapse of the arteries and are easily and directly obtained from histological sections, using a light microscope with a camera lucida attachment in conjunction with a microcomputer linked to a digitising board. The measurements produced are consistently repeatable. We considered that the extent of intimal change in a pulmonary artery was most readily understood when expressed not as an area measurement but in the form of an "intima index", in which intimal area is calculated as a proportion of the area enclosed by the internal elastic lamina in its theoretically unwrinkled state. Values for intima index range from greater than 0 to less than or equal to 1, indicating minimal through to total occlusion of the artery lumen. Although values for the intima index increased as artery size decreased in the subjects studied, there was no consistent overall correlation between intima index and artery size for different subjects. We therefore concluded that subjects should be compared by calculating mean intima indexes for arteries subdivided into groups according to size.